Ted Lambert : the man behind the paintings - Lambert, Ted (Theodore Roosevelt), 1905-approximately 1960 (University of Alaska Press, 2012)
Ted Lambert is regarded as one of the premier Alaska artists, a true pioneer. Born in 1905, and raised in the Chicago area, Lambert moved to Alaska in 1925 and went to work as a miner near McCarthy. He held several jobs, predominantly working at a copper mine and mushing dogs-first for adventure, and then as a mail carrier. Lambert left Alaska in 1931 to study art for a year at the American Academy of Art in Chicago, then moved to Seattle, where he began a mentorship under Eustace Ziegler, with whom he traveled throughout Alaska and painted. Eventually Lambert settled down in Fairbanks,